2008
DOI: 10.1016/j.jmb.2007.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Ribosome Recycling Factor Interactions with the 70S Ribosome

Abstract: SUMMARYAt the end of translation in bacteria, ribosome recycling factor (RRF) is used together with Elongation Factor G (EF-G) to recycle the 30S and 50S ribosomal subunits for the next round of translation. In x-ray crystal structures of RRF with the Escherichia coli 70S ribosome, RRF binds to the large ribosomal subunit in the cleft that contains the peptidyl transferase center (PTC). Upon binding of either E. coli or T. thermophilus RRF to the E. coli ribosome, the tip of ribosomal RNA helix H69 in the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
49
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 53 publications
7
49
1
Order By: Relevance
“…Recent studies have shown that ribosomes isolated from a strain lacking RluD show defects in the ability of RF2 (but not RF1) to catalyze the release of a peptide on UAA-programmed ribosome complexes (14). Finally, other studies observed large conformational changes in H69 in ribosome structures where ribosome recycling factor is bound, consistent with the idea that movement of the helix plays a critical role in the dissociation reaction that ribosome recycling factor catalyzes (9). Simple positioning makes H69 an excellent candidate for participation in substrate selection events and overall ribosome function.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Recent studies have shown that ribosomes isolated from a strain lacking RluD show defects in the ability of RF2 (but not RF1) to catalyze the release of a peptide on UAA-programmed ribosome complexes (14). Finally, other studies observed large conformational changes in H69 in ribosome structures where ribosome recycling factor is bound, consistent with the idea that movement of the helix plays a critical role in the dissociation reaction that ribosome recycling factor catalyzes (9). Simple positioning makes H69 an excellent candidate for participation in substrate selection events and overall ribosome function.…”
mentioning
confidence: 61%
“…Structural studies of tRNA (2)(3)(4)(5), release factors (6 -8), and ribosome recycling factor (9,10) bound to the ribosome reveal that H69 2 of the large subunit rRNA makes extensive contacts with all of these factors. This universally conserved helix forms an intersubunit bridge that is proximal to the substrate binding cleft and directly contacts the functionally critical h44 of 16 S rRNA which contains two of the three nucleotides known to directly interact with the decoding helix (codon-anticodon) during tRNA selection (A1492 and A1493).…”
mentioning
confidence: 99%
“…The interaction of RRF with the ribosome has been studied by directed hydroxyl radical footprinting on ribosomal RNA (Lancaster et al 2002), by cryo-EM (Agrawal et al 2004;Gao et al 2005;Barat et al 2007;Gao et al 2007), and by X-ray crystallography (Wilson et al 2005;Borovinskaya et al 2007;Weixlbaumer et al 2007;Pai et al 2008). RRF is bound at the interface between the subunits where it interacts mainly with the 50S subunit.…”
Section: Ribosome Disassembly As An In Vivo Target Of Fusidic Acidmentioning
confidence: 99%
“…23 In the cocrystal structures of ribosomes with various translation factors, bridge B2a has been seen interacting with parts of IF2, eukaryotic translation elongation factor 2, release factor 2, release factor 3 and ribosome recycling factor. [24][25][26][27][28][29][30] These interactions suggest that bridge B2a could be involved in regulating the activity of the translation factors when they are bound to the 70S ribosome during protein synthesis. One of the best-characterized interactions of B2a is with translation termination factors.…”
Section: Introductionmentioning
confidence: 99%